Cyathea ruttenbergii, a new tree fern (Cyatheaceae, Polypodiopsida) from Puerto Rico - Tejedor, Adrian; Areces-Berazain, Fabiola (Phytotaxa, 2018)
A new species, Cyathea ruttenbergii, is described from the Caribbean island of Puerto Rico. The new species differs from congeners by its large, lanceolate pinnules with wide sinuses and long attenuate apices, ovate lamina with 6–7 pinna pairs, bicolorous petiole scales, strongly armed petioles, and lack of indusium. The affinities and ecology of the species are discussed.